The Unfinished Project of Roncarelli v. Duplessis: Justiciability, Discretion, and the Limits of the Rule of Law - Sossin, Lorne (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
Roncarelli is remembered fifty years later particularly because of Justice Rand’s now iconic statement that “there is no such thing as absolute and untrammelled discretion.” Justice Rand defined “untrammelled discretion” as circumstances where action can be taken on any ground or for any reason that can be suggested to the mind of the decision maker. This statement has been understood to mean that all public regulation exercised through discretionary decision-making by executive officials has legal boundaries, and that the role of the courts is to ensure that decisions do not exceed those boundaries.In this paper, the author explores several areas of public regulation in Canada that remain “untrammelled”. These areas include realms of government action deemed to be non-justiciable, such as decisions involving foreign relations or the conferral of honours. The author argues that areas of untrammelled discretion are inconsistent with the Supreme Court of Canada’s reasoning in Roncarelli. To complete the unfinished project of Roncarelli, the author argues that all discretionary decisions should be understood to have justiciable elements, which include, at a minimum, a requirement that public power be exercised in good faith. The author concludes by highlighting that while approaching all discretionary authority as justiciable is intended to alter the approach of Canadian public law, Roncarelli’s project is as much a political project as a legal one.